ANALISA TITIK KRITIS GERAKAN ROLL KAPAL TRIMARAN UNTUK DIAPLIKASI PADA KAPAL IKAN PURSE SEINE - Fella Gaspersz; Richard B. Luhulima (ALE Proceeding, 2021)
The marine fisheries catching and processing industry are considered vulnerable to the effects of extreme weather at sea. Global warming effects and El Nino and La Nina have a significant impact on the upwelling process, which impacts the lifestyle and environment of marine biota, including pelagic fish, which is one of the most important contributors to the shipping industry. Extreme weather conditions, with wave heights ranging from 1 to 5 meters, dominate the waters of Maluku. In extreme sea conditions, most fishers choose not to go fishing, not because there are no fish at the fishing grounds, but to avoid mishaps at sea. This research aimed to analyze the critical point of ship roll motion and ship stability. The hull shape employed in this study was a monohull fishing vessel and a trimaran fishing vessel with the same displacement of 21,1 tons. In extreme weather conditions, the Maxsurf software was used to analyze the ship's response, especially the critical point of the ship's roll motion. The I.M.O. Standard was utilized to calculate the ship's stability. The operational speed of the ship was v = 3 knots, with fluctuations in wave angle of incidence between 00 - 1800. Wave heights of 1,0; 2,0; 3,0, and 0,4 meters represent extreme weather conditions in Maluku waters' fishing grounds. The findings revealed that the trimaran hull type had better stability where the inclination angle of trimaran vessel stability was 480 while the monohull was 410. The trimaran fishing vessel was able to withstand a wave height of 3 meters with an inclination angle of 32,560. In comparison, the monohull fishing vessel was able to survive at a wave height of 2 meters with an inclination angle of 24,690. Monohull fishing vessel had a maximum limit of roll motion at wave directions 82 and 99 with a wave height of 3 m, and it reached at the critical point at angles of 43 and 138, at the height of 4 m. Meanwhile, the trimaran fishing vessel had a critical point at a wave angle of 760 and 1000 with a wave height of 4 meters. In the area between those two angles, monohull and trimaran fishing vessels will lose the balance (stability) of the roll motion, resulting in capsize.